Diagnosis of coeliac sprue in adulthood - Matos Costa, João (2002)
Concepts about diagnosis of coeliac sprue have been changing in the past decade,namely recognising non-classical types of this disease, usually diagnosed in childhood. The development of serological tests with high specificity and sensitivity has lead to increased diagnosis of atypical or assymptomatic types, with consequent increase in incidence and prevalence of coeliac sprue.We report the case of a 25-year old woman admitted with general malaise, oedemas, 3-week long diarrhoea, recent childbirth with previous selective abortion of a twinpregnancy, intrauterine growth delay and oligoamnios. She had a previous medicalhistory of epilepsy since childhood, chronic anaemia in adolescence, and giardiasis.As an inpatient, the following tests were positive: D-xylosis for malabsorptionsyndrome, duodenal biopsy suggestive but not diagnostic for coeliac sprue.Autoantibody tests were positive for anti-gliadin IgA and IgG, anti-reticulin and antiendomysium.She clinically and histologically improved on a gluten-free diet. The autoantibody titre also diminished.A correlation is established between the obstetrical occurences and the circumstances in which the diagnosis was made.Coeliac sprue should be included in the work-up for diarrhoea in the adult, even in older ages. The diagnosis, once considered, is easy and cheap. It’s an example of newparadigms of Internal Medicine, as advances in laboratory diagnosis lead us toreappraise clinical reasoning, and reach new conclusions.